2014
DOI: 10.1142/s021830131450089x
|View full text |Cite
|
Sign up to set email alerts
|

Nonmesonic weak decay dynamics from proton spectra of Λ-hypernuclei

Abstract: A novel comparison between the data and the theory is proposed for the nonmesonic (NM) weak decay of hypernuclei. Instead of confronting the primary decay rates, as is usually done, we focus attention on the effective decay rates that are straightforwardly related with the number of emitted particles. Proton kinetic energy spectra of 5 Λ He, 7 Λ Li, 9 Λ Be, 11 Λ B, 12 Λ C, 13 Λ C, 15 Λ N and 16 Λ O, measured by FINUDA, are evaluated theoretically. The Independent Particle Shell Model (IPSM) is used as the nucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…From previous works of Refs. [54,55,58,65,75,76], we know that to describe the NMWD in Λ hypernuclei with open-shell cores within the IPSM it is enough to make the replacementĴ 2 /ĵ 2 Λ → F j N J in the decay-rate expression with the DCSC, where F j N J is a spectroscopic factor. Making the same replacements here, i.e.Ĵ 2 /ĵ 2…”
Section: Decay Ratementioning
confidence: 99%
See 1 more Smart Citation
“…From previous works of Refs. [54,55,58,65,75,76], we know that to describe the NMWD in Λ hypernuclei with open-shell cores within the IPSM it is enough to make the replacementĴ 2 /ĵ 2 Λ → F j N J in the decay-rate expression with the DCSC, where F j N J is a spectroscopic factor. Making the same replacements here, i.e.Ĵ 2 /ĵ 2…”
Section: Decay Ratementioning
confidence: 99%
“…[53]. Recently, it was suggested that the π + K meson-exchange model with soft monopole form factors could be a good starting point to describe this type of interaction in light and medium systems [54,55]. The lifetime of the free charmed baryon Λ + c is τ Λ + c = (2.00 ± 0.06) × 10 −13 s, which corresponds to the decay rate Γ(Λ + c → all) = (3.29 ± 0.10) × 10 −9 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…In what follows we will make use of analogies with nonrelativistic calculations. From previous works [21][22][23][24][25][26][27] done by our group, we know that to describe the hypernuclei with open-shell cores within the IPSM it is enough to do the following replacement in Eq. ( 48)…”
Section: B Hypernuclei With Open-shell Cores and Without Recoilmentioning
confidence: 99%
“…The NMWD dynamics is frequently handled by onemeson-exchange (OME) models. Such models are motivated by the fact that the N N interaction at long distance is due to the one-pion-exchange, but with the difference that in NMWD the exchange processes occur with one strong and one weak vertex and can include other mesons in addition to the π, like the pseudoscalar (K, η) and vector (ρ, ω, K * ) mesons [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The coupling constants at the strong vertices can be taken from different OME models for the N N interaction, while those at the weak vertices can be extracted from free Λ decay data and making use of soft meson theorems and SU (6) W symmetry [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation